The Role of Hippo/YAP Signaling in Alveolar Repair and Pulmonary Fibrosis - Gokey, Jason J.; Patel, Saawan D.; Kropski, Jonathan A. (Frontiers in Medicine, 2021)
Pulmonary fibrosis is characterized by loss of normal alveoli, accumulation of pathologic activated fibroblasts, and exuberant extracellular matrix deposition that over time can lead to progressive loss of respiratory function and death. This loss of respiratory function is associated with the loss of alveolar type 1 cells (AT1) that play a crucial role in gas exchange and the depletion of the alveolar type 2 cells (AT2) that act as progenitor cells to regenerate the AT1 and AT2 cell populations during repair. Understanding the mechanisms that regulate normal alveolar repair and those associated with pathologic repair is essential to identify potential therapeutic targets to treat or delay progression of fibrotic diseases. The Hippo/YAP developmental signaling pathway has been implicated as a regulator of normal alveolar development and repair. In idiopathic pulmonary fibrosis, aberrant activation of YAP/TAZ has been demonstrated in both the alveolar epithelium and activated fibroblasts associated with increased fibrotic remodeling, and there is emerging interest in this pathway as a target for antifibrotic therapies. In this review, we summarize current evidence as to the role of the Hippo-YAP/TAZ pathway in alveolar development, homeostasis, and repair, and highlight key questions that must be resolved to determine effective strategies to modulate YAP/TAZ signaling to prevent progressive pulmonary fibrosis and enhance adaptive alveolar repair.